Количественные характеристики оптического излучения, проходящего через задымленную среду - Surikov, Андрей; Leshenyuk, Николай; Petukhov, В. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2011)
Brief characteristics of test equipment and technique on assessment of light-extinction coefficient of combustion (smoldering) generated by aerosol have been presented. Results of analysis of more than 500 materials tests with a view to attenuation of laser radiation passing though the smoke developed in consequence of their combustion (smoldering) have been given. Materials which combustion (smoldering) attenuates the radiation of He-Ne laser in maximum have been specified. Assessment of light-extinction coefficient of smoke has been done.